Bridging the banking sector with the real economy: a financial stability perspective - Adrian Costeiu; Florian Neagu (European Central Bank (ECB), 2013)
This paper builds a macro-prudential tool designed to assess whether the banking sector is adequately prepared to orderly withstand losses resulting from normal or stressed macroeconomic and microeconomic scenarios. The link between the banking sector and the real sector is established via the corporate sector channel. The macro-prudential tool consists of a two-step approach. In the first step, we build a model for the probability of default (PD) in the corporate sector, so as to quantify oneyear ahead developments in the quality of banks' corporate loans. The framework is established using micro data, with a bottom-up approach. The second step consists of bridging the PD model with a macroeconomic module in order to capture the feedback effects from the macroeconomic stance into the banking sector, via the corporate sector channel. The macro-prudential tool is tested on the Romanian economy.
Keywords: G32; G21; E17; 330; financial stability; macro-prudential analysis; probability of default; ROC